PENGGUNAAN ASAP CAIR KAYU LABAN (VITEX PUBESCENS VAHL) SEBAGAI PENGENDALI PENYAKIT BUSUK BENIH TUSAM (PINUS MERKUSII JUNGH ET DE VRIESE) - Purba, Cerita Bernita; Oramahi, Hasan Ashari; dina, Wah; Diba, Farah (Universitas Tanjungpura, 2015)
The research aims to determine the effect of soaking pinus seeds with liquid smoke to the seedling growth and to obtain the optimal soaking period and pyrolysis temperature of liquid smoke in controlling fungi growth on pine seeds. Pyrolysis temperature used were 3500C, 4000C and 4500C, and seed soaking period were 2 hours, 4 hours and 6 hours before planting. It was found that optimal pyrolysis temperature for controlling fungi growth on pine seedling was 4500C and optimal soaking period was 6 hours before planting. Key word :Pinus merkusii, liquid smoke, Laban wood, seedling growth.